Oesophageal pseudodiverticulum after foregut duplication cyst excision: Case report and literature review - Bobanga, Iuliana D. (Afr J Paediatr Surg, 2016)
Oesophageal pseudodiverticula rarely occur after excision of benign oesophageal neoplasms. While management and outcomes have been reported in the adult leiomyoma literature, sparse data exist on the occurrence and management of pseudodiverticula after foregut duplication cyst excision. We discuss our experience with a paediatric patient and review relevant literature regarding operative techniques and surgical outcomes.